What Happens in the Eucharist? - Ford, David (Scottish journal of theology, 1995)
The eucharist or holy communion or mass or Lord's supper is probably the ritual most participated in and most discussed in human history. It is the principal act of worship of the majority of the billion and a half or so Christians in the world today and has some importance for most of the minority. Simply as an inquiry about what happens around the world at present my title would clearly be an impossible question to answer with anything approaching thoroughness. But that might seem an odd way to take it. In theology the question usually leads in to discussing real presence, eucharistic sacrifice, valid ministry and so on. Those are of course important, but I am reluctant to forget about inquiry into actual practice. I will not be able to contribute much on the subject, but it is a significant part of the imaginative context of this paper. So I will start by trying to begin to do justice to it. That will be the springboard for an attempt in Part 2 to redescribe the Eucharist in relation to some New Testament statements, without pretending that the intervening thousands of years that have generated all that diversity have not occurred. The main concerns there will be imperatives, especially the imperative of death, and Jesus as an agent of incorporation, a critical concept being that of non-identical repetition. Part 3 will take up some of the suggestions of Part 2 in order to develop one aspect of the Eucharist and transformation: what might some characteristics of a ‘eucharistic self’ be? The conclusion will then try to summarise the answer that has emerged to the title question.